LEARNING AS A LIFE STRATEGY - Bogusławska-Tafelska, Marta (Acta Neophilologica, 2005)
The goal of the paper is to explore the life-long specificity of the educational process, with special attention devoted to a vast collection of the psycholinguistic and ecolinguistic variables which orchestrate one's education. The dynamics and complexity of the foreign language education, in the context of the Polish university, ask for the twofold psycholinguistic treatment, that is, for the intraorganism strategic competence and behaviour; and for the interpersonal intervention, in the form of the educational offer and individually designed classroom work. The study proposes a redefinition of the learning process, which may constitute the starting point of a revised methodological framework in the context of the university foreign language education.